(untitled) (The Review of Diabetic Studies, 2025)
Background: Dental assistants are integral to the efficiency and quality of dental care delivery, yet their job satisfaction and career development opportunities remain underexplored in Saudi Arabia. Understanding these factors is essential for improving workforce stability and aligning with Saudi Vision 2030 goals for healthcare transformation. Aim: This narrative review examines the current state of job satisfaction and career development among dental assistants in the Saudi dental sector, identifying key influencing factors, interrelationships, challenges, and policy implications. Methods: A narrative review methodology was employed, with literature sourced from PubMed, Scopus, Web of Science, Google Scholar, and the Saudi Digital Library. Studies published between 2010 and 2025 in English or Arabic were included if they addressed job satisfaction, workplace conditions, training, or career progression of dental assistants in Saudi Arabia. Relevant international literature was also reviewed for comparative insights. Results: Findings indicate moderate overall job satisfaction among Saudi dental assistants, with higher satisfaction in teamwork and patient interaction, but lower satisfaction in salary progression and career advancement opportunities. Factors influencing satisfaction include work environment, compensation, workload, interpersonal relationships, and recognition. Career development is hindered by limited specialization options, unequal access to continuing professional development (CPD), and non-standardized promotion pathways. The review highlights a clear link between accessible career growth opportunities and higher job satisfaction levels. Conclusion: Enhancing job satisfaction and career development for dental assistants in Saudi Arabia requires standardized career frameworks, expanded CPD accessibility, and adoption of international best practices adapted to local needs. These measures would not only improve workforce retention but also support the delivery of high-quality dental care in line with national healthcare objectives.